ANALISIS SEMIOTIKA PADA IKLAN POCARI SWEAT “SAAT SUHU TUBUH NAIK, JAGA CAIRAN TUBUH DENGAN POCARI SWEAT” - Tania, Sarah Dwi (ASKARA: Jurnal Seni dan Desain, 2024)
Pocari Sweat is a drink product that replaces ION or body fluids. To promote its products, Pocari Sweat produces various advertisements that can add 9 products in a creative way. One of them is the Pocari Sweat advertisement entitled "When the Body Temperature Rises, Take Care of Body Fluids with Pocari Sweat" which is one of the creative advertisements from Pocar Sweat which has meaning in every scene in the advertisement. Each scene has certain signs and certainly has a certain meaning as well. To find out the meaning of the Pocari Sweat advertisement, use Roland Barthes' semiotic approach. The writer concludes that there are denotative and connotative meanings in advertisements. The meaning of the denotation obtained in the advertisement is a child who has a nightmare meeting a dragon that makes fires everywhere. This has a connotative meaning which means that someone who is sick certainly needs adequate rest. Even in a resting state, the body's performance continues to run and sweat. Sweat is a body fluid that needs to be in line with the amount of sweat that is released. So Pocari Sweat is a solution to replace lost body fluids.